The Effect of Different Types of Egg Yolk in Tris Diluent on the Quality of Frozen Semen of Brahman Cattle - Suharyati, Sri; Hartono, Madi; Siswanto, Siswanto; Febriyansar, Eri; Sirat, Muhammad Mirandy Pratama (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This study was conducted at the Regional Technical Service Unit for Artificial Insemination, Lampung District, Terbanggi Besar Subdistrict, Central Lampung Regency, Lampung Province, from January 25 to 30, 2023. The objective of this research was to determine the effect of different types of egg yolk and to identify the best type of egg yolk in tris diluent on the quality of frozen semen of Brahman cattle. The experimental design used was a Completely Randomized Design with three treatments: standard egg yolk, herbal egg yolk, and omega-3 enriched egg yolk, each with six replications. The data obtained were analyzed using ANOVA at the 5% and 1% significance levels, and if significant, further analyzed with Duncan’s Multiple Range Test. The results showed that the different types of egg yolk in tris diluent had no significant effect (P>0.05) on post-thaw spermatozoa abnormalities, had a significant effect (P<0.05) on post-thaw spermatozoa motility, and had a highly significant effect (P<0.01) on the percentage of live spermatozoa post-thawing. The conclusion of this study was that the addition of standard egg yolk and omega-3 enriched egg yolk in tris diluent has a better effect on the motility and percentage of live spermatozoa of Brahman cattle compared to the addition of herbal egg yolk.